2009
DOI: 10.1074/jbc.a808126200
|View full text |Cite
|
Sign up to set email alerts
|

Rnd1 regulates axon extension by enhancing the microtubule destabilizing activity of SCG10.

Abstract: We suggest that subscribers photocopy these corrections and insert the photocopies in the original publication at the location of the original article. Authors are urged to introduce these corrections into any reprints they distribute. Secondary (abstract) services are urged to carry notice of these corrections as prominently as they carried the original abstracts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…Other studies have also found that SCG10 levels are increased proximal to the site of traumatic injury in both the central and peripheral nervous systems (38)(39)(40). This SCG10 accumulation in the end bulbs of the proximal stump may be functionally important for axonal regeneration, because SCG10 within growth cones encourages the outgrowth of developing axons (23,(41)(42)(43). Of note, increased levels of SCG10 correlate closely with axon regeneration and sprouting after axon severing and ischemic brain injury (44)(45)(46).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Other studies have also found that SCG10 levels are increased proximal to the site of traumatic injury in both the central and peripheral nervous systems (38)(39)(40). This SCG10 accumulation in the end bulbs of the proximal stump may be functionally important for axonal regeneration, because SCG10 within growth cones encourages the outgrowth of developing axons (23,(41)(42)(43). Of note, increased levels of SCG10 correlate closely with axon regeneration and sprouting after axon severing and ischemic brain injury (44)(45)(46).…”
Section: Discussionmentioning
confidence: 92%
“…During development SCG10 is required for axonal microtubules to be sufficiently dynamic to sustain axon outgrowth. When SCG10 levels are decreased, microtubule dynamism dwindles, and neurite outgrowth is restricted (41,42). Excessive microtubule stability also disrupts adult axons: Pharmacological microtubule stabilizers such as taxol induce axonal degeneration (47) and cause neuropathy in patients (48).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, there are to date no data arguing for or against this hypothesis. Nevertheless, the two families of MT destabilizing proteins in neurons, the stathmin and kinesin 13 families, have been studied in some detail, and although their function in axon guidance has not been defined, they do affect axon outgrowth and branching (Homma et al 2003; Suh et al 2004; Morii et al 2006; Tararuk et al 2006; Poulain and Sobel 2007; Li et al 2009). Interestingly, it appears that their destabilizing activity must be tightly regulated: too much and MT levels in the neurons fall, inhibiting outgrowth; too little and MTs grow to the tips of growth cones and form looped structures, also resulting in less outgrowth due to growth cone pausing.…”
Section: Microtubule-associated Proteins In Axon Guidancementioning
confidence: 99%
“…The microtubule destabilizing factors, stathmin, superior cervical ganglia neural-specific 10 (SCG10), and SCG10-like protein (SCLIP) are highly expressed in nascent neurons, and represent a target of cellular signaling pathways to modulate microtubule dynamics in neurons. [173][174][175][176] Stathmin/ SCG10 family of proteins can destabilize microtubules and increase catastrophes by sequestering free tubulin and preventing its association with microtubule plus ends or by associating with tubulin on microtubule plus ends. 177,178 It appears an intricate balance of stathmin/SCG10 expression/activity is necessary for optimal neurite growth since neurons depleted of SCG10 or highly overexpressing it show reduced neurite growth.…”
Section: Building a Neurite-microtubulesmentioning
confidence: 99%